Integrasi Mindful, Meaningful, dan Joyful Learning dalam Mewujudkan Pembelajaran Humanis di Era Digital - Alvan Satria Shidiq; Yunsimaranti; Siska Novita; Elsa Mardian; Iswardi; Demina (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The rapid development of digital technology and the use of artificial intelligence (AI) in education has the potential to increase academic pressure, reduce learning focus, and reduce humanistic interactions between teachers and students at the high school level. This study aims to examine the integration of mindful learning, meaningful learning, and joyful learning approaches in realizing humanistic learning in the digital era at the senior high school level. The study used a qualitative method with a case study approach implemented in one high school. Data were collected through observations of the learning process, interviews with teachers and students, and documentation studies. In addition, a literature review was used to strengthen the analysis of the concepts and implementation of the three learning approaches. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the integration of mindful learning, meaningful learning, and joyful learning can improve learning focus, student engagement, relate the material to real life, and create a more enjoyable learning atmosphere. The humanistic learning that is formed is characterized by increased respect for students' voices, reflective abilities, and the development of critical and creative thinking patterns in the learning process.